Pain-related synaptic plasticity in spinal dorsal horn neurons: role of CGRP - Willis William D; Adwanikar Hita; Fu Yu; Han Jeong S; Bird Gary C; Neugebauer Volker (SAGE Publishing, 2006)
Abstract Background The synaptic and cellular mechanisms of pain-related central sensitization in the spinal cord are not fully understood yet. Calcitonin gene-related peptide (CGRP) has been identified as an important molecule in spinal nociceptive processing and ensuing behavioral responses, but its contribution to synaptic plasticity, cellular mechanisms and site of action in the spinal cord remain to be determined. Here we address the role of CGRP in synaptic plasticity in the spinal dorsal horn in a model of arthritic pain. Results Whole-cell current- and voltage-clamp recordings were made from substantia gelatinosa (SG) neurons in spinal cord slices from control rats and arthritic rats (> 6 h postinjection of kaolin/carrageenan into the knee). Monosynaptic excitatory postsynaptic currents (EPSCs) were evoked by electrical stimulation of afferents in the dorsal root near the dorsal root entry zone. Neurons in slices from arthritic rats showed increased synaptic transmission and excitability compared to controls. A selective CGRP1 receptor antagonist (CGRP8-37) reversed synaptic plasticity in neurons from arthritic rats but had no significant effect on normal transmission. CGRP facilitated synaptic transmission in the arthritis pain model more strongly than under normal conditions where both facilitatory and inhibitory effects were observed. CGRP also increased neuronal excitability. Miniature EPSC analysis suggested a post- rather than pre-synaptic mechanism of CGRP action. Conclusion This study is the first to show synaptic plasticity in the spinal dorsal horn in a model of arthritic pain that involves a postsynaptic action of CGRP on SG neurons.